Laparoscopic Treatment of Placenta Percreta Retention in a Cesarean Scar: A Case Report - Jean-Bernard, Dubuisson (Frontiers in Surgery, 2014)
Placenta percreta retention within the scar of a previous cesarean section is rare. We report here one of these cases treated successfully by laparoscopy, with uterine repair. Different therapeutic options are described.